Sistem Pendukung Keputusan Pemilihan Taksi Berbasis Web dengan Algoritma Pencarian Linear - Bimo Satriantoro; Ni Made Satvika Iswari (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
Indonesian people have a high interest for public transportation. There are few kind of public transportation, and taxi is one of them. Taxi use taximeter to calculate passanger fares. Taximeters between taxi companies are different in term of results although using the same equation and principle. The total fare from the taximeter is based on equation that includes distance variable, speed of the vehicle, and time variable. People have a problem to choose taxi because of the differnces of taximeter fares and taxi pool. Based on the problem, the solution is an application to help customer to decide choosing taxi. The application will help customer by giving informations about taximeter and carpool form two different company. The informations are based on the distance of the start point and the finish point of the customer and based on the distances of the customer and the carpool of the taxy company that will processed trough the application to calculating the total fares for the customer between two taxi companies. By using algorithm for linear searching, customer will get the informations to help them to decide which taxi the customer will use. Keywords: Linear Algorithm, Taximeter, Google Apps, Choice, Taxi